2020
DOI: 10.5897/ajar2019.14391
|View full text |Cite
|
Sign up to set email alerts
|

Management of the legume pod borer Maruca vitrata Fabricius (Lepidoptera: Crambidae) with field applications of the entomopathogenic fungus, Beauveria bassiana and a mixed formulation of the baculovirus MaviMNPV with emulsifiable neem oil

Abstract: The present study assessed the effectiveness of the entomopathogen fungus Beauveria bassiana in comparison with neem oil combined with the baculovirus MaviMNPV and a synthetic insecticide deltamethrin for the control of Maruca vitrata Fabricius under field conditions. The trial was conducted in six villages at Glazoue and Djakotomey, two districts in Benin. Four treatments consisting of (1) untreated control, (2) neem + MaviMNPV, (3) B. bassiana and (4) deltamethrin were arranged in a complete randomized block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Furthermore, enzymes and other compounds like beauvericin, which are partly produced using the hosts' resources are also reported to equip EPF with the ability to disrupt the insects' regular functions with immune systems in particular and ultimately result in their deaths. A similar observation was also made by Mehinto et al (2020) and Mnyone et al (2011), who also found that the EPF, B. bassiana applied to legume pod borer, Maruca vitrata Fabricius (Lepidoptera: crambidae) and Anopheles gambiae respectively were gradually killed from the second day following applications as opposed to quicker actions by their positive controls' counterparts.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, enzymes and other compounds like beauvericin, which are partly produced using the hosts' resources are also reported to equip EPF with the ability to disrupt the insects' regular functions with immune systems in particular and ultimately result in their deaths. A similar observation was also made by Mehinto et al (2020) and Mnyone et al (2011), who also found that the EPF, B. bassiana applied to legume pod borer, Maruca vitrata Fabricius (Lepidoptera: crambidae) and Anopheles gambiae respectively were gradually killed from the second day following applications as opposed to quicker actions by their positive controls' counterparts.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, the conventional synthetic insecticide, Banophos 720 EC (20 ml/20 L) has shown quick knockdown of S. frugiperda larvae compared to EPF formulations and negative controls respectively. This is because they underwent thorough improvements which make them more effective and broad-spectrum (Mehinto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, its efficacy can be increased when applied with neem oil and neem, Azadirachta indica, and Jatropha curcas extracts (Joelle et al, 2020;Sokame et al, 2015;Srinivasan et al, 2009).…”
Section: Biopesticidesmentioning
confidence: 99%